Persepsi Masyarakat terhadap Dampak Limbah Tahu di Sekitar Sungai - Shaskia, Nina; Yunita, Irda (Tameh, 2021)
The tofu processing sector is quickly expanding in tandem with the popularity of tofu meals among Indonesians. Unfortunately, the tofu industri's rapid growth has not been matched by effective waste management, and as a result, many businesses continue to dump liquid waste directly into rivers without treatment. In the Krueng Daroy and Krueng Doy River sections of Banda Aceh, there are three tofu factories that directly dump liquid waste into the river and have the potential to damage the river. As a result, the goal of this study is to examine the public's perception of tofu waste's influence on the river ecosystem and to assess public comprehension of tofu waste's impact on the environment. The descriptive analysis method was used in this study. Questionnaires, observations, and interviews were used to gather information. After that, the data was descriptively processed and weighted. The findings are divided into three categories: public perception of aesthetics, public perception of smell, and public perception of the environmental impact of tofu waste. More than 90% of the respondents thought that tofu waste had a negative impact on the environment's aesthetics and produced stink. The public's impression of tofu waste in the river environment is 78.56 percent, which means that more than 75 percent of respondents believe tofu waste has an environmental impact. It is included in the "disturbing" category based on the average attitude rating of 785.6. This demonstrates that tofu waste has a detrimental environmental impact. As a result, business actors must get a better understanding of the impact of tofu waste on the environment, as well as the efforts that must be done to reduce that impact, such as constructing an appropriate Waste Treatment Plant (IPAL) or repurposing tofu liquid waste for other purposes.